Karakteristik Peserta Didik dan Pembelajaran Mendalam: Sebuah Kajian Teoretis dan Empiris - Ahmad Arif; Alda Anggraini; Irma Amalia; Rohana Rohana (Pancasila and Civics Education Journal, 2026)
Abstract: The diversity of student characteristics encompasses physical, intellectual, behavioral, achievement, and emotional dimensions. Teachers' understanding of this diversity is the main foundation for creating truly student-centered deep learning. Methods: This article was compiled through a literature review analyzing Gardner's theory of multiple intelligences, Bandura's social cognitive learning theory, Maslow's hierarchy of needs, and various recent empirical findings from journals published between 2021 and 2025. Results: Individual student differences include aspects of intelligence, talent, learning styles (visual, auditory, kinesthetic), interests, and social background. At the high school level, visual learning styles were the most dominant (37%), followed by kinesthetic (33%) and auditory (29%), while 51% of students were in the low interest category. Deep learning implemented through diagnostic assessments, a variety of teaching methods, and the creation of a supportive learning environment has proven effective in improving students' conceptual understanding and motivation to learn. The main obstacles faced are the lack of teacher training on individual differences and the disparity in facilities and infrastructure between schools. Conclusion: In-depth learning based on learner characteristic profiles is no longer an option, but a necessity in 21st-century educational practices.Keywords: Student Characteristics, Individual Differences, In-Depth Learning, Multiple Intelligences, Independent CurriculumAbstrak: Keberagaman karakteristik peserta didik mencakup dimensi fisik, intelektual, perilaku, prestasi, maupun emosional. Pemahaman guru terhadap keragaman ini menjadi fondasi utama terciptanya pembelajaran mendalam (deep learning) yang benar‑benar berpusat pada siswa. Metode dalam penelitian ini disusun melalui studi pustaka dengan menganalisis teori kecerdasan majemuk Gardner, teori belajar sosial kognitif Bandura, hierarki kebutuhan Maslow, serta berbagai temuan empiris mutakhir dari jurnal terbitan 2021–2025. Adapun hasil penelitian menemukan bahwa perbedaan individu siswa meliputi aspek kecerdasan, bakat, gaya belajar (visual, auditori, kinestetik), minat, dan latar belakang sosial. Pada jenjang SMA, gaya belajar visual paling dominan (37%), diikuti kinestetik (33%) dan auditori (29%); sementara itu 51% siswa berada pada kategori minat rendah. Pembelajaran mendalam yang dijalankan melalui asesmen diagnostik, variasi metode pengajaran, serta penciptaan lingkungan belajar yang suportif terbukti efektif dalam meningkatkan pemahaman konseptual sekaligus motivasi belajar siswa. Kendala utama yang dihadapi adalah minimnya pelatihan guru tentang perbedaan individu serta ketimpangan sarana dan prasarana antarsekolah. Kesimpulan: Pembelajaran mendalam yang didasarkan pada profil karakteristik peserta didik bukan lagi pilihan, melainkan keharusan dalam praktik pendidikan abad ke‑21.Kata Kunci: Peserta Didik; Perbedaan Individu; Pembelajaran Mendalam; Kecerdasan Majemuk; Kurikulum Merdeka